Evaluation of Antioxidant and Antibacterial Activity of Gelatin Nanoparticles with Bitter Orange Peel Extract for Food Applications - Adamaris García-Juárez; Alba Mery Garzón-García; José Rogelio Ramos-Enríquez; José Agustín Tapia-Hernández; Saúl Ruiz-Cruz; Dalila Fernanda Canizales-Rodríguez; Carmen Lizette Del-Toro-Sánchez; Francisco Rodríguez-Félix; Víctor Manuel Ocaño-Higuera; José de Jesús Ornelas-Paz (Foods)
Bitter orange is a citrus fruit rich in bioactive compounds, but its waste is currently underutilized. One potential solution is to encapsulate these bioactive compounds. This research aims to synthesize gelatin nanoparticles loaded with an ethanolic extract of bitter orange peel and to evaluate their in vitro antioxidant and antibacterial activities. Coaxial electrospray was used to encapsulate the ethanolic extract of bitter orange with bovine gelatin as wall material, considering a voltage of 15 kV, a wall solution flow rate of 0.1 mL/h, and a core solution flow rate of 0.08 mL/h. Characterization of the nanoparticles was performed using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). Antioxidant activity was evaluated by the total phenolic content, flavonoids, and antioxidant capacity by the DPPH•, ABTS•+, and FRAP assays. Antibacterial activity was assessed by the well diffusion technique on Mueller–Hinton agar against Listeria monocytogenes and Escherichia coli O157:H7 bacteria. SEM images confirmed that the nanoparticles were spherical in shape, while FT-IR analysis indicated that the incorporation of the extract did not alter the amide bonds of the gelatin protein. The nanoparticles containing the extract exhibited higher antioxidant activity and heightened inhibition against E. coli O157:H7, indicating their potential food applications.